The Effect of Local Application of Magnesium Oxide Powder on the Blood Parameters During Nerve Regeneration of Injured Sciatic Nerve in Rat - Helal Montaser; Hussein Aseel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Peripheral nerves injuries are very common defects in animals which may lead to loss of sensory andmotor functions of the nerve. These defects are highly corrected using nanotechnology. This studyaimed to find out the effect of applying local application of magnesium Nano- and Microparticles onthe level of magnesium and rat nerve group factor in rat during the process of nerve regeneration. Thisstudy included sixty adult male apparently healthy Wistar rats had bodyweight average (M±SD: 230± 20) gram. Random division to three group was done as: Controlgroup (CG), Nanogroup (NG) andMicrogroup (MG) of (n=20) each after transecting the sciatic nerve and instant proximal and distal endof the sciatic nerve suturing. First group the (Controlgroup) which had no interferences after suturing;the second group (Nanogroup) had a local application of nanoparticles powder of MgO on sutured sitein addition to third group (Microgroup) had a local application of microparticles powder of MgO onthe sutured site. The results showed that a significant and continuous increase of rat growth factor to beseen in Nanogroup and Microgroup however, Microgroup had the highest level to the end of the study,while no significant correlation between the three groups and level of Mg during the study was seen. Itis concluded that MgO forms of Micro and Nano particles have a positive effect on nerve regenerationwhich can be determined by significant increase of NGF in Microgroup then Nanogroup but not inControlgroup. In addition to that using low dose of local application of Nano and Microparticle has nosystemic toxicity on body.